ALGERIAN ARABIC AND TAMAZIGHT ETYMOLOGIES - Nadia GHOUNANE & Hanane RABAHI (Ziglôbitha)
Abstract : The contact between Arabic and Tamazight resulted in a set of loanwords introduced to the varieties of both languages due to the continuous contact since the arrival of the Arabs around 700 AD. As such, this linguistic situation makes it hard for scholars to explore early and later words integrated into their varieties. To this end, the main aim of the current research is to shed light on existing etymologies in both Algerian dialectal Arabic and Tamazight varieties. Secondly, it also intends to explore the semantic distribution of these words through a corpus analysis of the Tamazight dialect spoken in the Bejaia and Tlemcen varieties used in the Beni Bousaid region. The results revealed that Tamazight varieties imported many loanwords from Standard Arabic. The analysis also demonstrated that a set of lexicons still exists in the Tlemcen variety of the Beni Bousaid region. By analyzing loanwords in the Beni Bousaid dialect, the researchers found that most belong to Tachelhit. The findings confirmed phonological and morphological borrowings into Algerian Arabic spoken in the Beni Bousaid region taken from Tamazight. Moreover, the analysis showed that the contact between Tamazight and Algerian-spoken Arabic impacts stress placement.